Funkcjonowanie osób z niepełnosprawnością przez pryzmat kondycji psychicznej członków rodziny - Konarska, Joanna (Kultura-Społeczeństwo-Edukacja, 2023)
The article is based on fragments of the results of many years of research conducted under the direction of the author, situated in the context of research on the family of people with disabilities and chronic diseases. The main trend of the research was to diagnose the psychological condition of people who have long-term care obligations for a family member by learning about the factors that create the quality of life, life satisfaction, the recognized system of values and its relationship with the health and mental state of the charges. In these studies, an interesting thread turned out to be the knowledge of the relationship between the rehabilitation progress of the charges, changes in their psyche, especially in self-esteem and in the value system, and analogous changes in the mentality of caregivers. The article presents such relationships not only among carers of people with disabilities, but also among able-bodied siblings, who, although not directly burdened with the care of a family member, indirectly feel the effects of a changed and unusual family situation, also incurring the psychological costs of this situation. This is a very important problem in the context of holistic rehabilitation, and family members of people requiring constant care are not covered by any systemic therapeutic assistance. The examined relationships clearly indicate that both the rehabilitation progress of people with disabilities and the mental state of their family members are interdependent, and the rehabilitation process is not only carried out in direct relationship with professionals, but mainly in the family itself, and it is the family members who permanently create the conditions for motivating to overcome barriers related to disability. Therefore, their mental condition is of great importance for improving the functioning of a family member who requires care.